Analysis of Employee Readiness in the Transition to Regional Financial Digitalization: A Case Study of the Implementation of SIPD at the North Sumatra Provincial Department of Industry and Trade - Br Kesogihin, Mika Mutiara; Syawalia, Nabila; Ompusunggu, Juslena; Nidiaty, Putri; Sianturi, Minarta Juani Aulia; Irawan, Irawan (CV Raskha Media Group, 2025)
The transition from manual systems or previous applications to the Regional Government Information System (Sistem Informasi Pemerintahan Daerah/SIPD) represents a strategic step toward a more integrated, accountable, and transparent digitalization of regional financial governance. The implementation of SIPD requires adequate human resource readiness, particularly among financial management personnel, to ensure the system can be operated optimally and sustainably. This study aims to analyze employees' readiness to face the transition toward financial digitalization through the implementation of SIPD at the Department of Industry and Trade of North Sumatra Province. This research employs a qualitative, descriptive approach. Data were collected through direct observation, documentation, and in-depth interviews with SIPD operators and regional financial managers involved in financial planning and reporting processes. Data analysis was conducted thematically to describe the actual condition of employee readiness and to identify challenges encountered during the system implementation. The findings indicate that, from a functional perspective, the implementation of SIPD has improved the speed and structure of financial planning document preparation, such as the Work and Budget Plan (RKA) and Budget Implementation Document (DPA). However, regarding employee readiness, several significant challenges remain. These include limited technical understanding of new system features and menus, relatively short duration of technical training sessions, and dependence on the stability of the central server, which often disrupts workflow. Although employees generally demonstrate adaptive attitudes toward digital transformation, strengthening human resource competencies through continuous training and ensuring a stable technological infrastructure are critical to the success of this transition. This study recommends more intensive technical assistance to minimize data input errors and enhance the efficiency of regional financial reporting.